Banking Resilience in Times of Financial Crisis: A Comparative Regulatory Analysis - Heru Kurniawan; Ratna Sari Dewi (Capitalis: Journal of Economic Stability, Banking, and Investment, 2026)
This study empirically investigates the determinants of banking resilience during systemic financial crises through a cross-country comparative analysis encompassing both advanced and emerging economies over the 2015–2023 period. Utilizing a balanced panel of commercial and Islamic banks, resilience is operationalized as a multidimensional construct encompassing capital adequacy, liquidity sufficiency, profitability stability, and risk containment. The research employs dynamic panel GMM estimations to address endogeneity, persistence, and heterogeneity, incorporating regulatory stringency indices, sustainability orientation metrics, and bank-specific controls. Findings indicate that higher capital buffers and liquidity coverage ratios significantly enhance crisis-period stability, while ESG-oriented strategies reinforce long-term resilience, particularly in jurisdictions with stringent supervisory frameworks. Islamic banking models exhibit differential sensitivity to regulatory interventions, suggesting that financial architecture and governance play pivotal roles in mediating systemic shocks. Moreover, disparities between advanced and emerging economies underscore the interaction between macroeconomic conditions and institutional quality. The results provide robust empirical evidence for policymakers, highlighting the importance of harmonized regulatory standards and sustainable finance practices in mitigating crisis-induced vulnerabilities.